Dinamika Uang Panai’ dalam Perkawinan Suku Bugis Makassar di Sentani, Papua: antara Tradisi dan Realitas Sosial: Dynamics of Uang Panai in Bugis Makassar Marriages in Sentani, Papua: Between Tradition and Social Reality - karim karim; Faisal Faisal; Hendra Yulia Rahman; Pratiwi Aurina Herman Sumantri; Nur Atika (ISTIDLAL, 2026)
This study examines the dynamics of Uang Panai’ in the marriages of the Bugis Makassar ethnic group in Sentani, Papua: between tradition and social reality, focusing on how the tradition of Uang Panai’ evolves, how it is practiced, and the social and economic impacts arising from its implementation.The research employs a qualitative method, with data collected through observation, interviews, and documentation involving customary actors, families of prospective brides and grooms, and community leaders of the Bugis-Makassar.The findings show that Uang Panai’ remains an important tradition that determines social status and family dignity, with the amount determined based on factors such as lineage, education, occupation, and the economic condition of the bride. The practice of Uang Panai’ has significant social impacts, serving as a symbol of prestige as well as a source of family pride, but it can also cause delays or even prevent marriage if its demands are not met. Economically, Uang Panai’ often becomes a heavy burden for prospective grooms, encouraging them to migrate or increase their income before marriage.These findings reveal a negotiation between efforts to preserve tradition and adapt to the socio-economic realities of the local community, showing that the practice of Uang Panai’ has undergone changes in value and meaning in the context of migration and cultural acculturation in Papua.